EFEKTIVITAS PEMELIHARAAN ASET DI KOMPLEKS SEKRETARIAT UKM BARAT DAN TIMUR - Afifah Rashif; Ria Arifianti (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to evaluate the effectiveness of fixed asset maintenance, particularly buildings, in the UKM West and East Secretariat Complex at Universitas Padjadjaran Jatinangor. The evaluation was conducted using three indicators of effectiveness: timeliness, appropriateness, and efficiency. The findings indicate that asset maintenance has been carried out on schedule, met user needs, and utilized the budget efficiently. However, challenges such as limited funding and insufficient user participation in maintaining the facilities remain. To address these issues, this study recommends the establishment of standard operating procedures (SOPs) for damage reporting, improved coordination among stakeholders, and optimized budget allocation. These improvements are expected to enhance the sustainability and efficiency of asset management. The results of this study serve as a reference for better and more effective asset maintenance practices in the future.